Perbedaan Kadarkolesterol Pada Pasien Diabetes Melitus Tipe II Yang Disertai Hipertensi Dengan Tanpa Hipertensi Di RSUD Sukoharjo - Yuniati, Kurnia; , dr. Sumardjo Sp.PD; , dr. Listiana Masyita Dewi, M.Sc (2015)
Background: Indonesia that number 4 ranking as the country with the highest number of people with diabetes mellitus in the world according to the WHO. Diabetes mellitus patient with hypertension is higher risk factor of cardiovasculer diseases than without hypertension. Diabetes mellitus and hypertension associated with dyslipidemia who have the characteristic of elevated triglyceride, reduce level of of HDL cholesterol LDL cholesterol levels. Purpose: Knows the difference of cholesterol levels in patients with type II diabetes mellitus with hypertension and without hypertension. Method: This research use cross sectional design in RSUD Sukoharjo at December 2014. Subject of the research are 50 patients who were divided into 25 people of type II diabetes mellitus patients with hypertension and 25 people type II diabetes mellitus patients without hypertension at interna disease poly in RSUD Sukoharjo. Source of data obtained from medical record by purposive sampling method. Data analyze in this research use t test. Result: the result obtained means of cholesterol level in type II diabetes mellitus patients with hypertension are 184,16±30,644 and type II diabetes mellitus patients without hypertension are 223,56±51,403 with p value = 0.002 (p < 0,05 ). Conclusion: From the result can conclusion there is difference significance cholesterol level between type II diabetes mellitus patients with hypertension and without hypertension.